Influence of heat damage on the bolted double lap joint strength of pultruded E-glass/polyester composites. (June 2021) - Toubia, Elias A.; Alomari, Abdalla; Morgan, Alexander B.; Klosterman, Donald
Abstract: Continued operation of thermally degraded composite joints due to fire or over-temperature events could result in a catastrophic failure. This experimental study evaluates the residual strengths and failure mechanisms of bolted double lap pultruded joints in regions of low-to-moderate heat induced exposure. Test parameters included, flat plate thickness, heat flux exposure, and load direction with respect to the member's pultrusion axis. Post-mortem micrograph, SEM, and X-ray CT images highlighted the nature of the damage as related to observed strengths' reductions. Plate thickness and load direction are key parameters influencing the residual strength and failure modes of thermally degraded pultruded joints. Highlights: Pultruded joints followed by low intensity fire-induced damages are presented. Results show that thermal damage can, and does change, the residual strength. Plate thickness and load direction are key parameters influencing the failure modes. Thin plate showed the highest reduction when load applied along the pultrusion axis. Presented data supports "Pultruded GFRP structural reliability" efforts.